2014
DOI: 10.1111/liv.12460
|View full text |Cite
|
Sign up to set email alerts
|

The p53 mutation spectrum in hepatocellular carcinoma from Guangxi, China : role of chronic hepatitis B virus infection and aflatoxin B1 exposure

Abstract: P53 mutations were detected in 223 HCC samples, 13 adjacent liver tissue samples and only 1 of 68 normal liver tissue samples. The mutation sites concentrated at exon 4, 5, 6, 7, 8, 9 and no mutation was detected in exon 1, 2, 3, 10 and 11. The most frequently occurring mutation was in codon 249 (R249S) in exon 7. Patients in the HBV(+)/AFB1(+) and HBV(-)/AFB1(+) groups had significantly higher mutation rates compared with patients in the HBV(+)/AFB1(-) and HBV(-)/AFB1(-) groups. P53 mutation status and HBV/AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 42 publications
3
59
0
1
Order By: Relevance
“…Accumulative, long-term interactions between environmental and genetic factors lead to the occurrence and progression of HCC (31). Although a number of tumor suppressor genes and oncogenes, including KRAS, PTEN and TP53, have been identified to be involved in HCC progression (6,7,32), the molecular mechanism of HCC is not completely understood. In recent years, the focus of tumor research has expanded to investigate the potential tumor suppressive or oncogenic functions of lncRNAs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulative, long-term interactions between environmental and genetic factors lead to the occurrence and progression of HCC (31). Although a number of tumor suppressor genes and oncogenes, including KRAS, PTEN and TP53, have been identified to be involved in HCC progression (6,7,32), the molecular mechanism of HCC is not completely understood. In recent years, the focus of tumor research has expanded to investigate the potential tumor suppressive or oncogenic functions of lncRNAs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Well-known risk factors for acquiring HCC include chronic infection with hepatitis B (HBV) or C (HCV) virus, increasing incidence of obesity leading to liver inflammation, and prolonged dietary consumption of aflatoxins. More recently, it has been shown that the relative risk for the development of HCC is increased synergistically among individuals exposed to both aflatoxins and HBV (2,3) and among HCV-positive individuals with increased alcohol consumption (4). The incidence of HCC is expected to increase significantly in the next decade, mainly due to the increasing number of patients infected with chronic HCV and non-alcoholic steatohepatitis (NASH) especially in Western countries.…”
mentioning
confidence: 99%
“…The most frequent mutations in the TP53 gene are: crossing G: C to T: A transversion at the codon 249 and C: T to A: T and C: G to T: A at the codon 250 [9,10]. In some studies a correlation has been observed between TP53 gene expression and survival of patients with HCC.…”
Section: Introductionmentioning
confidence: 93%